2006
DOI: 10.1021/ef0603986
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Inherent Metallic Species as a Crucial Factor for Kinetics of Steam Gasification of Char from Coal Pyrolysis

Abstract: Four pairs of raw and acid-washed brown coals were subjected to pyrolysis and in-situ steam gasification at 900 °C in fixed-bed reactors with or without forced gas flow through the bed of char particles. The chars from the acid-washed coals were gasified obeying a first-order kinetics with respect to the fraction of unconverted char regardless of the presence/absence of forced gas flow. Its presence/absence considerably influenced the gasification kinetics of the chars from the raw coals, even altering the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 27 publications
5
75
0
Order By: Relevance
“…An equation with the same type of function as eq 6 can be derived by another kinetic model that considers the progress of non-catalytic gasification and AAEM-catalyzed gasification in parallel. 47,48 The rate of gasification is expressed by…”
Section: Resultsmentioning
confidence: 99%
“…An equation with the same type of function as eq 6 can be derived by another kinetic model that considers the progress of non-catalytic gasification and AAEM-catalyzed gasification in parallel. 47,48 The rate of gasification is expressed by…”
Section: Resultsmentioning
confidence: 99%
“…At high temperatures (900e1200 C), the dramatic volatilization of Na (up to 80%) was accompanied by increases in tar yield during the pyrolysis of the Na-form samples [30], as shown in Figure 5. Kitsuka [31] also proved that forced gas flow through the bed of char particles could diminish the amount of alkali metal during steam gasification at 900 C, thereby causing completely different changes in the char conversion over time. Quyn et al [10] suggested that the high mobility of Na allows it to migrate onto the char surface to catalytically active species such as eOeNa and/or Na clusters, thus improving char reactivity.…”
Section: Figurementioning
confidence: 98%
“…Catalytic carbon gasification with external alkali and alkaline earth metals (AAEMs) or with internal AAEMs in coal or biomass has been extensively documented [22][23][24][25][26][27][28][29]. It is well known that calcium species are, in general, not catalytically remarkable in gasification of medium-to-high rank coal at such a low temperature as used for potassium carbonate [20].…”
Section: Introductionmentioning
confidence: 99%